A study to determine the correlation between transverse cerebellar diameter and gestational age among the pregnant women in second and third trimester - Shivaraj Ananthareddy; Raveendra D. Totad; Shwetha Hitnal; Shankarsnehit B. Patil (Al Ameen Medical College, 2023)
Background: With advent of ultrasound, fetal changes are efficiently illustrated by ultrasonography with the evolving parameters as indicators of intrauterine growth. Methods: A prospective study was conducted on pregnant women in second and third trimester presented to the Department of Radio Diagnosis, Navodaya Medical College Hospital and Research Centre, Raichur. Result: Study results showed that TCD and GA was highly correlated with BPD, FL, AC and HC with p-value < 0.0001. Conclusion: It was concluded that TCD and GA was well correlated with various ultrasonic parameters including BPD, FL, AC, HC and TCD. The correlation between GA and TCD in IUGR pregnancies was highly significant with (R2 =0.85).